An empirical study of EIA litigation involving energy facilities in Chile and Colombia (2019)
In Latin America, as elsewhere, environmental and participatory rights have been expanding, and EIAs have been central to those efforts. In response, litigation against EIAs has increased as communities turn to the courts to exercise these rights, raising fears among developers that costs associated with EIAs and resulting litigation are excessive and a deterrent on economic growth. In many jurisdictions, including Chile and Colombia, these fears have prompted reforms to streamline EIA procedures. This study empirically examines the frequency and results of litigation against EIAs in Chile and Colombia for developers, communities, and state agencies. We compiled two databases of litigation against energy facilities that received EIA licenses between the 1990s/2000 (when EIAs were first required) and 2016. Because some, but not all, energy facilities are contested, this sector is ideal for examining litigation trends. Using descriptive and cross-tabular statistics, our analysis echoes recent research that finds that few EIAs are litigated in court. Litigation is a fundamental tool for civil society organizations seeking to safeguard environmental and participatory rights, although the number of cases invoking these rights remains smaller than for other reasons. Practices across Chile and Colombia differ regarding what kinds of cases individuals bring and the rate at which courts accept cases brought by civil society organizations or corporations. Past litigation trends also suggest that a shift towards renewable energy sources could lead to a decrease in litigation. © 2019